ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP KELAS IX - Mardotillah Angelina; Kiki Nia Sania Effendi (IKIP Siliwangi, 2021)
This study aims to determine how the mathematical connection ability of junior high school students. This research was conducted at one of the junior high schools in Cikarang Utara District with the research subjects of class IX 5 students at the junior high schools. This research uses a descriptive qualitative approach. The instrument used in this study was a test of mathematical connection ability in the form of a description consisting of 3 items arranged based on indicators of mathematical connection ability. The data collection technique used in this study was to provide 3 questions to test the mathematical connection ability of the SPLDV material. The data analysis technique used in this study was the data analysis technique proposed by Miles and Huberman which consisted of data reduction, data presentation, and conclusion drawing. The results of this study were 2 students were in the high category, 22 students were in the medium category, and 5 students were in the low category. So it can be concluded that the mathematical connection ability of class IX 5 students at the school in solving SPLDV questions is in the medium category.